1983
DOI: 10.1507/endocrj1954.30.311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of .GAMMA.-aminobutyric acid on excitability of tubero-infundibular neurons in rat hypothalamic slices.

Abstract: The effect of ƒÁ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We believe that the method, reported here, for estimation of in vitro activity of TIDA neurons is a useful means for studying the regulatory mechanisms of neurosecretory activity of TIDA neurons. Furthermore, it would become possible to compare and correlate changes in the neurosecretory activity of TIDA neurons with those in the neuronal excitability [32] using in vitro hypothalamic slices.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the method, reported here, for estimation of in vitro activity of TIDA neurons is a useful means for studying the regulatory mechanisms of neurosecretory activity of TIDA neurons. Furthermore, it would become possible to compare and correlate changes in the neurosecretory activity of TIDA neurons with those in the neuronal excitability [32] using in vitro hypothalamic slices.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of estrogen treatments on the responsiveness of ARC neurons to these agents were also examined, since it has been shown that electrical activity of ARC neurons is affected by estrogen (MAGI, 1973) and that estronge implantation in the ARC causes a change in hormone secretion from the anterior pituitary (AKEMA et al, 1983). A preliminary report of a portion of this study has already been presented (NISHIHARA et al, 1983).…”
mentioning
confidence: 99%